FISH WEIGHTING PROCESS AT LAMPULO FISH AUCTION PLACE IN BANDA ACEH CITY IN MA'QUD 'ALAIH PERSPECTIVE - Alfata (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2018)
Fish Auction Place (TPI) in Lampulo, Banda Aceh, is the largest place of loading and unloading fish in Aceh. However, it has not succeeded in providing the best service to consumers. The accuracy of the scales used by traders is often unclear in weighing fish so that consumers are disadvantaged. The results of the study revealed that the process of weighing fish in TPI Lampulo was inaccurate in term of the scale measurement, and rounding of the scales had been practiced to gain more benefits for the traders yet disadvantages the consumers. Furthermore, the fish traders who sell fish in large quantities do not pay attention to the containers when weighing. Fish weighing containers are sometimes wet or dry, a dry container weighing approximately 2.8 kilograms or 3 kilograms for the wet one. The fish traders in TPI lampulo Banda Aceh rounded the weight to 3 kilograms, meaning 0.2 kilograms of loss for consumers. According to some traders, it had become customary. It can be concluded that the process of weighing the fish at TPI Lampulo Banda Aceh was not accurate in term of measuring the scales. Abstrak: Tempat Pelelangan Ikan di Lampulo Kota Banda Aceh, merupakan tempat yang terbesar di Aceh dimana bongkar muat ikan, namum dengan begitu belum bisa memberikan pelayanan yang terbaik kepada konsumen, pedagang dalam menimbang ikan belum jelas keakuratan timbangan sehingga konsumen merasa dirugikan. Dari hasil penelitian ditemukan proses penimbangan ikan di TPI Lampulo tidak akurat takaran timbangannya, dan pembulatan ukuran timbangan sudah menjadi kebiasaan demi mendapatkan keuntungan bagi pedagang yang merugikan konsumen, para pedagang ikan yang menjual ikan dalam jumlah yang banyak ketika melakukan penimbangan tidak memperhatikan wadah tempat penimbangan ikan. Wadah tempat penimbangan ikan kadang kala basah atau kering. Terdapat perbedaan berat wadah yang kering mencapai 2,8 kilogram ketika basah wadah tersebut mencapai 3 kilogram. Para pedagang ikan di TPI lampulo Kota Banda Aceh membulatkan menjadi 3 kilogram terdapat 0,2 kilogram kerugian bagi konsumen. Menurut beberapa pedagang hal tersebut sudah menjadi kebiasan. Berdasarkan uraian di atas dapat disimpulkan bahwa proses penimbangan ikan yang tejadi di TPI Lampulo Banda Aceh tidak akurat takaran timbangan. Kata kunci: Proses, Timbangan, TPI, Ma’qud ‘Alaih.